Occupational therapy practice to the elderly with orthopedic condition in an emergency hospital - Loureiro, Helena Auler; Silva, Kênia Lara; Braga, Marcela Aline Fernandes (Revista de Terapia Ocupacional da Universidade de São Paulo, 2020)
Objective: To analyze the Occupational Therapy (OT) practice with the orthopedic alterations elderly in an urgency and emergency hospital. Methods: Retrospective longitudinal study with 125 hospitalized due to orthopedic alterations aged patients in an urgency and emergency hospital in Belo Horizonte, attended by the OT of the Orthopedic team, hospitalized after the structuring of the OT in Orthopedics service, from March 2015 to April 2016. The sociodemographic, clinical, functional and specifics procedures of OT. The descriptive analysis of the material was carried out. Results: A higher incidence of fracture was found in females. The femoral fracture had a higher frequency, followed by fractures of the upper limb. The main interventions performed by OT were educational intervention, intervention in mental functions, adaptive intervention and restorative intervention of the activity basic body position change. The hip revision was the orthopedic procedure with the highest average number of OT visits. Conclusions: The OT focuses its interventions with this population on the prevention and/or treatment of possible complications, which can increase hospital stay time and generate greater functional decline for the elderly, reducing their functionality in home environment.